Hubungan Antara Motivasi dengan Perilaku Self Medication dalam Pencegahan Kekambuhan Gastritis pada Pasien di Puskesmas Ranotana Weru Kota Manado - Kurrota Ayun Paputungan, Farel; D. Kandou, Grace; T. Ratag, Budi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Gastritis is a common health problem in Indonesia, including in Manado City. Many patients manage gastritis symptoms through self-medication, often using over-the-counter and limited OTC drugs. This reflects a level of awareness but also underscores the need for proper education on drug selection, dosage, usage timing, and expiration awareness. Motivation plays a key role in influencing health decisions, including efforts to prevent gastritis recurrence. However, studies examining the link between motivation and self-medication behavior remain limited. This study aims to analyze the relationship between motivation and self-medication behavior in preventing gastritis recurrence among patients at Ranotana Weru Public Health Center, Manado City. It used a quantitative analytic observational method with a cross-sectional design. From a population of 123, a total of 94 respondents were selected as samples. Data were collected using validated and reliable questionnaires and analyzed using the Pearson correlation test in SPSS. Results showed a significant relationship between motivation and self-medication behavior (p = 0.015, r = 0.251), indicating a weak but positive correlation. Higher motivation was associated with a greater tendency to engage in self-medication as a preventive measure. However, self-medication should not be the first-line response. Professional medical consultation remains essential, especially if symptoms persist or worsen. Thus, education on the proper use, risks, and limitations of self-medication is crucial to support safer and more informed health decisions.